Efek Sitotoksik Formula Jamu Daun Sirsak, Buah Takokak, dan Umbi Bidara Upas terhadap Sel Kanker Payudara MCF-7 - Widiyastuti, Yuli; Marfuatush Sholikhah, Ika Yanti; Haryanti, Sari (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
Cancer is one of the leading cause of death in the world. Complicated and high cost treatments of cancer encourages people to look for alternative treatments among others using medicinal plants. Some medicinal plants that are empirically claimed to have anticancer effect are soursop (Annona muricata), takokak (Solanum torvum), and bidara upas (Merremia mammosa). However, these medicinal herbs have not been tested for cytotoxic activity against MCF-7 cancer cells. The purpose of this study was to determine the cytotoxic activity of the anticancer herbal formula consisting those three plants. The effect of each single extract and the combination formula were tested for their activity on cell viability of MCF-7 with MTT assay method. The herbal formula with the most active combination of medicinal plant extracts was further tested for its activity on the expression of Bcl-2 protein by immunocytochemistry methods. The results showed that each single extract and the combination formula gave cytotoxic effect on MCF-7 breast cancer cells. Formula A, consisted of a mixture of soursop leaves, takokak fruit, and bidas upas bulb with a ratio of 1:1:1, results in highest inhibition of the viability of MCF-7 cells with IC50 values of 48 µg/ml. The formula also enhances the apoptosis process in MCF-7 cells which is shown by decreasing the expression of antiapoptotic Bcl-2 proteins.